Introduction to Nursing Informatics - Hannah, Kathryn J.; Ball, Marion J.; Edwards, Margaret J.A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2006)
This series is directed to healthcare professionals who are leading the tra- formation of healthcare by using information and knowledge. Launched in 1998 as Computers in Health Care, the series offers a broad range of - tles: some addressed to speci?c professions such as nursing, medicine, and health administration; others to special areas of practice such as trauma and radiology. Still other books in the series focus on interdisciplinary issues, such as the computer-based patient record, electronic health records, and networked healthcare systems. Renamed Health Informatics in 1998 to re?ect the rapid evolution in the discipline now known as health informatics, the series will continue to add titles that contribute to the evolution of the ?eld. In the series, eminent experts, as editors or authors, offer their accounts of innovations in health informatics. Increasingly, these accounts go beyond hardware and software toaddresstheroleofinformationinin?uencingthetransformationofheal- caredeliverysystemsaroundtheworld.Theseriesalsowillincreasinglyfocus on “peopleware” and the organizational, behavioral, and societal changes that accompany the diffusion of information technology in health services environments. These changes will shape health services in the new millennium. By m- ing full and creative use of the technology to tame data and to transform information, health informatics will foster the development of the kno- edge age in health care. As coeditors, we pledge to support our professional colleaguesandtheseriesreadersastheyshareadvancesintheemergingand exciting ?eld of Health Informatics.
Foundations of Nursing Informatics -- Nurses and Informatics -- Anatomy and Physiology of Computers -- History of Healthcare Computing -- Telecommunications and Informatics -- Nursing Use of Information Systems -- Enterprise Health Information Systems -- Nursing Aspects of Health Information Systems -- Applications of Nursing Informatics -- Clinical Practice Applications: Facility Based -- Clinical Practice Applications: Community Based -- Administration Applications -- Education Applications -- Research Applications -- Infrastructure Elements of the Informatics Environment -- Nursing Data Standards -- Defining Information Management Requirements -- Selection of Software and Hardware -- Data Protection -- Ergonomics -- Disaster Recovery Planning -- Implementation Concerns -- A Process Redesign Approach to Successful IT Implementation -- Professional Nursing Informatics -- Nursing Informatics Education: Past, Present, and Future -- The Future for Nurses in Health Informatics.
Keywords: Health informatics; Nursing; Health Informatics; Nursing